S-allylCysteine Ester/Caffeic Acid Amide Hybrids as Promising Antiprotozoal Candidates: Synthesis, Biological Evaluation and Molecular Modeling Studies - Wilson Cardona-G; Sara Maria Robledo; Laura Juliana Prieto; Andrés Felipe Yépes (Universidade de São Paulo, 2022)
Abstract In order to overcome the challenges of discovering new antiprotozoal drugs, we synthesized a new class of hybrids based on S-allylCysteine Ester/Caffeic Acid Amide and evaluated four of them against Trypanosoma cruzi and Plasmodium falciparum. Hybrid 6 exhibited good activity on T. cruzi with an EC50 value of 5.45 µM, whereas hybrid 3 was active over P. falciparum with an EC50 of 18.08 µM. All hybrids displayed a good selectivity index on P. falciparum. Molecular docking computations indicated that several hybrids have good binding affinities towards the protozoa related enzymes (Cruzipain or Falcipain-2) when compared against current inhibitors. In silico studies showed that conjugates 1-3 and 6 fulfilled optimal ADME characteristics, suggesting them as safe alternatives for oral treatment of protozoal infections.